NEW FOSSILS OF SUIDAE (MAMMALIA, ARTIODACTYLA) FROM THE HASNOT LATE MIOCENE, NORTHERN PAKISTAN - A. Batool; M. A. Khan; N. A. Qureshi (Journal of Animal and Plant Sciences, 2015)
A variety of suids from the Dhok Pathan Formation of the Middle Siwaliks are identified, described and discussed in this paper. The new remains were recovered from the Late Miocene continental deposits, located in the vicinity of the Hasnot village, Jhelum district, Punjab province, Pakistan. A three suid species namely Propotamochoerus hysudricus, cf. Hippohyus sivalensis and Hippopotamodon sivalense have been identified. A documentation of the new remains is the objective of this paper.
Keywords: Suids; Artiodactyla; Vertebrates; Late Miocene; Hasnot; Siwaliks